2018
DOI: 10.1021/acs.macromol.8b00582
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Performance of an Open-Shell Donor–Acceptor Conjugated Polymer Doped with a Radical-Containing Small Molecule

Abstract: Thermoelectric devices based on conducting polymers are promising energy conversion systems; however, the intrinsic semiconducting nature inherent to the macromolecular architecture of common conjugated polymers (CPs) in their neutral form requires doping to impart electrical conductivity and requires optimization of the complex dopant–polymer interactions in order to enhance thermoelectric performance. Therefore, designing and synthesizing CPs that have readily tunable properties and that can be doped in a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 56 publications
1
55
1
Order By: Relevance
“…[ 30,31 ] Strong, proquinoidal TQ acceptors lower the lowest unoccupied molecular orbital (LUMO) and facilitate strong intramolecular interactions, promoting very narrow bandgaps, a quinoidal bonding pattern, backbone rigidity, and unpaired spin densities. [ 26,27 ] Substitution of the TQ acceptor with methyl ( P1 ), phenyl ( P2 ), and thiophene ( P3 ) moieties affords the capability to fine‐tune structural and electronic features. The polymers were synthesized using a modified microwave‐assisted Stille cross‐coupling copolymerization between (4,4‐dihexadecyl‐4 H ‐cyclopenta[2,1‐ b :3,4‐ b ′]dithiophene‐2,6‐diyl)bis(trimethylsta‐nnane) [ 32 ] and 4,9‐dibromo‐6,7‐dimethyl‐[1,2,5]thiadiazolo[3,4‐ g ]quinoxaline [ 33 ] for P1 , 4,9‐dibromo‐6,7‐diphenyl‐[1,2,5]thiadiazolo[3,4‐ g ]quinoxaline [ 34 ] for P2 , and 4,9‐dibromo‐6,7‐di(thiophen‐2‐yl)‐[1,2,5]thiadiazolo[3,4‐ g ]quinoxaline [ 35 ] for P3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 30,31 ] Strong, proquinoidal TQ acceptors lower the lowest unoccupied molecular orbital (LUMO) and facilitate strong intramolecular interactions, promoting very narrow bandgaps, a quinoidal bonding pattern, backbone rigidity, and unpaired spin densities. [ 26,27 ] Substitution of the TQ acceptor with methyl ( P1 ), phenyl ( P2 ), and thiophene ( P3 ) moieties affords the capability to fine‐tune structural and electronic features. The polymers were synthesized using a modified microwave‐assisted Stille cross‐coupling copolymerization between (4,4‐dihexadecyl‐4 H ‐cyclopenta[2,1‐ b :3,4‐ b ′]dithiophene‐2,6‐diyl)bis(trimethylsta‐nnane) [ 32 ] and 4,9‐dibromo‐6,7‐dimethyl‐[1,2,5]thiadiazolo[3,4‐ g ]quinoxaline [ 33 ] for P1 , 4,9‐dibromo‐6,7‐diphenyl‐[1,2,5]thiadiazolo[3,4‐ g ]quinoxaline [ 34 ] for P2 , and 4,9‐dibromo‐6,7‐di(thiophen‐2‐yl)‐[1,2,5]thiadiazolo[3,4‐ g ]quinoxaline [ 35 ] for P3 .…”
Section: Resultsmentioning
confidence: 99%
“…Thin films of the polymers show absorption profiles with maxima (λ max ) of 1.60 μm ( P1 ), 1.45 μm ( P2 ), and 1.66 µm ( P3 ) and relatively sharp band‐tail characteristic of undoped polymers ( Figure a). [ 26 ] The optical bandgap ( E g opt ) of P1 is 0.57 eV, as estimated from the absorption onset of the thin film. Cyclic voltammetry shows that the HOMO is located at −4.93 eV and the LUMO at −3.90 eV, which gives an electrochemical bandgap ( E g elec ) of 1.03 eV (Figure 1b and Table S1 (Supporting Information)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently demonstrated that electronic states in this class of polymers can be tuned from closed-shell singlets to biradicaloids with varying amounts of open-shell character, to biradicals in singlet and triplet spin states. [28,30] Electron spin resonance spectra, collected at room temperature, shows a welldefined signal at g e = 2.006, indicating unpaired or weakly paired electrons ( Figure S2, Supporting Information). These results are consistent with density functional theory (DFT) calculations at the unrestricted (U)B3LYP/6-31+G** level of theory and basis set on an oligomer with four repeat units (n = 4).…”
Section: Synthesis and Solid-state Electrochemical Propertiesmentioning
confidence: 99%